Empowering diversity: A study connecting women in leadership to company performance in the canadian music industry - Women In Music Canada (Women In Music Canada)
Gender diversity in the music industry is low, both in Canada and internationally. The lack of diversity may represent a competitive disadvantage, as diversity is known to promote innovation and broad thinking, which is precisely what the music industry needs as it undergoes rapid change. This study, performed by Women in Music Canada in collaboration with PwC, assesses the impact of gender diversity of leadership within the Canadian music industry and the impact on company performance. Performance was assessed using estimates of annual revenue and revenue per employee, as well as relevant revenue-generating activities for a selection of Canadian firms. The study focused on companies within the Canadian music landscape and assessed organizations belonging to several industry sectors, such as publishers and record labels, managers and agents, and performance venues. The findings reflect the current state of the Canadian music industry and are benchmarked against international research conclusions. Overall, the study finds three main conclusions: 1. Gender diversity of leadership within the industry is low, at 28.1%, with only 9% of women performing as the head of the company. 2. Diversity of leadership impacts performance – we find that for every 10% increase in diversity, there is a 17.9% increase in revenue per employee. 3. Diversity of leadership also impacts quality of artist roster for music companies – a 10% increase in diversity leads to a 27.5% increase in live performance sales for a company’s artist roster. Live performance makes up the majority of Canadian music industry revenue, and there is a correlation between other forms of music industry revenue (streaming, album sales, etc.) and live performance sales. The results of the study suggest that the industry, including associations and government funders, need to support diversity.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; amériques; approches et analyses; canada; genre; inégalités; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail